A Nontoxic Case of Vitamin D Toxicity. Issue 2 (21st September 2015) - Chakraborty, Sutirtha; Sarkar, Ajoy Krishna; Bhattacharya, Chandramouli; Krishnan, Prasad; Chakraborty, Subhosmito
Abstract : Vitamin D toxicity also known as hypervitaminosis D was previously believed to be rare. But with an increase in vitamin D supplementation several cases have been reported in literature. Fat soluble vitamins like Vitamin D, due to their ability to accumulate in the body, have a higher potential for toxicity than water soluble vitamins. The main clinical consequence of vitamin D toxicity is hypercalcemia. In this report we describe an adult female patient who developed very high serum Vitamin D levels (746 ng/mL, RI: 20 to 50) as a result of medication error. Inspite of such high serum concentrations the patient was without any clinical symptoms and had normal serum calcium. We critically discuss the mechanism of toxicity and hypothesize the possible molecular/metabolic factors which might have been responsible for this nontoxic presentation. This case study highlights the fact that physicians need to consider the risk of medication errors while prescribing Vitamin D therapy. Clinical trials to study Vitamin D toxicity in humans is not possible ethically. Thus the evidence base regarding the safety profile of Vitamin D supplementation in humans has been build through case reports. This review of the paradoxical clinico-laboratory manifestation of hypervitaminosis D could possibly contribute to existing literature.